Dada Performance - Gordon, Mel (New York PAJ, 1987)
In the first collection of its kind, Mel Gordon brings together important texts by leading Dadaists Hugo Ball, Kurt Schwitters, Richard Huelsenbeck, Roger Vitrac, Tristan Tzara, Emmy Hennings, Francis Picabia, and others.
Bibliography: p. 165.
Keywords: 20th Century (1901-2000); Cultural history; Theater history; Europe